2021
DOI: 10.3390/ijms221810030
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Signaling Induces Cisplatin Resistance via Down-Regulating GULP1 Expression in Bladder Cancer

Abstract: The underlying molecular mechanisms of resistance to cisplatin-based systemic chemotherapy in bladder cancer patients remain to be elucidated, while the link between androgen receptor (AR) activity and chemosensitivity in urothelial cancer has been implicated. Our DNA microarray analysis in control vs. AR knockdown bladder cancer lines identified GULP1 as a potential target of AR signaling. We herein determined the relationship between AR activity and GULP1 expression in bladder cancer cells and then assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Based on retrospective clinical observations, the different molecular subtypes are prognostic of response (1,7,14,38). Recent studies have implicated a variety of pathways that contribute to chemoresistance including long noncoding RNAs (39,40), epigenetic pathways (41-47), miRNAs (48) and androgen signaling (44,(49)(50)(51)(52)(53). Based on previous observation that patients with stroma-rich subtype tumors have better prognosis as compared to those having the basal/squam subtype, the cisplatin response was evaluated in two BURP lines with molecular classifications of stromal-rich (BURP-16SR) and basal/squam (BURP-24BaSq).…”
Section: Discussionmentioning
confidence: 99%
“…Based on retrospective clinical observations, the different molecular subtypes are prognostic of response (1,7,14,38). Recent studies have implicated a variety of pathways that contribute to chemoresistance including long noncoding RNAs (39,40), epigenetic pathways (41-47), miRNAs (48) and androgen signaling (44,(49)(50)(51)(52)(53). Based on previous observation that patients with stroma-rich subtype tumors have better prognosis as compared to those having the basal/squam subtype, the cisplatin response was evaluated in two BURP lines with molecular classifications of stromal-rich (BURP-16SR) and basal/squam (BURP-24BaSq).…”
Section: Discussionmentioning
confidence: 99%
“…AR is the androgen receptor, and AR signalling pathway is related to many hormone-dependent diseases such as prostate cancer, 49 breast cancer [50][51][52] and ovarian cancer, 53 as well as malignant tumours, for example gastric cancer, 54,55 lung cancer, 56,57 bladder cancer, 58,59 F I G U R E 8 Potential signalling pathway of oridonin on gastric cancer constructed in the present research.…”
Section: Effects Of Oridonin On the Tgfβ Signalling Pathway In Sgc-79...mentioning
confidence: 79%
“…Before proceeding further, we first demonstrated that the results of drug response estimation are reliable. Cisplatin is a common therapeutic agent for bladder cancer patients, and a recent study showed that high GULP1 expression enhanced the sensitivity of patients to cisplatin ( Teramoto et al, 2021 ). We divided the patients into high and low expression groups according to the expression level of GULP1.…”
Section: Resultsmentioning
confidence: 99%